2019
DOI: 10.1634/theoncologist.2017-0666
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success of Phase II Pediatric Oncology Clinical Trials

Abstract: Background There are limited data to predict which novel childhood cancer therapies are likely to be successful. To help rectify this, we sought to identify the factors that impact the success of phase II clinical trials for pediatric malignancies. Materials and Methods We examined the impact of 24 preclinical and trial design variables for their influence on 132 phase II pediatric oncology clinical trials. Success was determined by an objective assessment of patient response, with data analyzed using Fisher's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…every drug has obtained registration and approval). These findings are similar to the results of a recent study which examined the impact of various variables for their influence on Phase 2 pediatric oncology clinical trials [19]. The authors found that Phase 2 trials initiated based on the results of adult trials were less likely to produce positive results.…”
Section: Discussionsupporting
confidence: 87%
“…every drug has obtained registration and approval). These findings are similar to the results of a recent study which examined the impact of various variables for their influence on Phase 2 pediatric oncology clinical trials [19]. The authors found that Phase 2 trials initiated based on the results of adult trials were less likely to produce positive results.…”
Section: Discussionsupporting
confidence: 87%
“…For example, CDC25-mediated dephosphorylation of CDC2 (also known as CDK1) activates the CDC2 and cyclin B complex. In MB cells exposed to 4-HPC, phosphorylated CDC2 Tyr 15 increased, indicating CDC2/cyclin B complex inhibition and stalled G 2 /M progression (fig. S4, A to C, lanes 1 and 6).…”
Section: Ly2606368 Blocks Dna Damage-induced Cell Cycle Checkpoint Signaling In Mb and Induces Apoptosismentioning
confidence: 95%
“…S3B, top). In addition, phosphorylation of CDC2 Tyr 15 , a downstream target of CHK signaling, was significantly reduced by treatment with any of the CHK1/2 inhibitors (fig. S3B, lower).…”
Section: Chk1/2 Inhibition Improves Mb Median Survival In Vivo With Ly2606368 the Best-in-class Inhibitormentioning
confidence: 97%
See 1 more Smart Citation
“…The authors did not report on toxicity,but noted that doses were delayed in some animals due to weight loss. The majority of early phase trials are unsuccessful and one reason is the misinterpretation of preclinical data and translatability of research findings [5]. We are concerned that the doses used in this study are not clinically achievable and thus are not able to be effectively translated to the clinic.…”
mentioning
confidence: 99%